Elimination of the Negative Component of the Unipolar Atrial Electrogram as an In Vivo Marker of Transmural Lesion Creation. (August 2015) - Bortone, Agustín; Brault-Noble, Guillaume; Appetiti, Anthony; Marijon, Eloi
<x xml:space="preserve">Abstract</x> Background— It has been experimentally shown that elimination of the negative component of the unipolar atrial electrogram (R morphology completion) during radiofrequency applications reflects transmural lesions creation. Subsequently, it has been clinically suggested that such a transmurality can be either irreversible or reversible. The present study is aimed to determine, at the histological level, whether transmural lesions, assessed by R morphology completion, might indeed be reversible in some circumstances or not. Methods and Results— In 6 Mongrel hound dogs, superior and inferior vena cavae were isolated and individual lesions were created in the right atrium using radiofrequency energy (30 W/48°C/17 mL/min as presettings and 10g of force in average) under CARTO guidance. Five types of lesions were created; R+0: termination of ablation at the time of R morphology completion; R+5, R+10, or R+20: extension of ablation for 5, 10, or 20 seconds, respectively, after R morphology achievement; and conventional: radiofrequency applications lasting 30 seconds irrespective of the atrial electrogram modification. All conventional, R+5, R+10, and R+20 lesions were necrotic and transmural, whereas some R+0 lesions were not (comprising a part of necrosis and a part of reversible cell damage). Interestingly, surrounding organ injuries were observed after conventional, R+10, and R+20 radiofrequency applications but were not observed after R+0 and R+5 applications. Conclusions— Elimination of the negative component of the unipolar atrial electrogram reflects, in general, irreversible transmural necrosis creation. In some cases, however, it translates transmural lesion only (with potential reversibility) likely related to transient cell damage creation.